Aktivitas Anticendawan Bacillus cereus 11UJ terhadap Rhizoctonia solani dan Pyricularia oryzae - Yadi Suryadi; I Made Samudra; Tri Puji Priyatno; Dwi Ningsih Susilowati; Puji Lestari; Sutoro Sutoro (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Microbial secondary metabolites is an important resource for antifungal development in disease control strategy. The objective of this study was to screen Bacillus cereus 11UJ, an antagonistic rhizosphere bacteria for potential secondary metabolite production against rice fungal pathogens, i.e. Rhizoctonia solani and Pyricularia oryzae. The antagonistic effect of crude exract was evaluated using sterile filter paper discs on PDA medium. The ethyl acetate extracts of the bacterium showed a better antifungal activity to P. oryzae than those of R. solani. The inhibitory effect of the filtrate proved the potency of the isolates to produce antifungal. Analysis of pyrolysis gas chromatography-mass spectrometry showed that B. cereus 11UJ produces 3 major compounds i.e; 9,19-cyclolanostan-3-ol, acetate, (3.beta.)- (CAS) cycloartanyl acetate (13.14%); 4-(2’,2’-dimethyl-6’-methyliden-1’-cyclohexyliden)-3-methyl-2-butanone (9.72%); and stigmast-5-en-3-ol oleat (9.09%) which suggested to play an important role in the suppression of rice fungal pathogens.